2018
DOI: 10.1088/1367-2630/aaa37c
|View full text |Cite
|
Sign up to set email alerts
|

Improving the phase response of an atom interferometer by means of temporal pulse shaping

Abstract: We study theoretically and experimentally the influence of temporally shaping the light pulses in an atom interferometer, with a focus on the phase response of the interferometer. We show that smooth light pulse shapes allow rejecting high frequency phase fluctuations (above the Rabi frequency) and thus relax the requirements on the phase noise or frequency noise of the interrogation lasers driving the interferometer. The light pulse shape is also shown to modify the scale factor of the interferometer, which h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…Due to the cavities’ long storage time with respect to the duration of the Bragg pulses, the interrogation fields will suffer some degree of deformation of their temporal amplitude profiles 69 . This deformation scales with the cavity finesse, and it can have an adverse impact on the interferometers by increasing the minimum interaction time of the velocity-selective atomic transitions as well as their power requirements 70 .…”
Section: Miga Antenna Designmentioning
confidence: 99%
“…Due to the cavities’ long storage time with respect to the duration of the Bragg pulses, the interrogation fields will suffer some degree of deformation of their temporal amplitude profiles 69 . This deformation scales with the cavity finesse, and it can have an adverse impact on the interferometers by increasing the minimum interaction time of the velocity-selective atomic transitions as well as their power requirements 70 .…”
Section: Miga Antenna Designmentioning
confidence: 99%
“…82 , was extensively used (with an extension to arbitrary pulse shapes presented in Ref. 83 ). These sources of noises can be reduced down to the mrad per shot level, well below the level of residual vibration noise, which still amounts to 10-100 mrad per shot, even with sophisticated vibration isolation schemes.…”
Section: Sensitivity Limitsmentioning
confidence: 99%
“…Various techniques have been developed in the field of nuclear magnetic resonance (NMR) spectroscopy to produce control pulses that are robust to variations in the interaction strength and detuning, and such techniques should be applicable to other systems, including the effective two-level schemes of atom interferometry. Shaped pulses [13][14][15], rapid adiabatic pulses [16][17][18], and composite pulses [19][20][21][22] all use complex time-dependent interactions to reproduce the desired operation of a single pulse while compensating for the effects of inhomogeneities. For atom interferometry, McGuirk et al [10] suggested that composite pulses could improve the augmentation pulses within large momentum transfer (LMT) arrangements, and Butts et al [12] demonstrated that the WALTZ [23] composite inversion pulse doubled the sensitivity of a cold Cs atom interferometer.…”
Section: Introductionmentioning
confidence: 99%